DIVIDING RISKS IN RAILWAY TRANSPORT (Perner's Contacts, 2009)
The article describes actual knowledge within the area of identification of risks in railway transport; dividing and grouping of the risks which threaten certain of a railway transport system.
Keywords: unsoundness; risk; railway transport